Relationship between serum HBV-RNA levels and intrahepatic viral as well as histologic activity markers in entecavir-treated patients - Wang, Jing; Yu, Yiqi; Li, Guojun; Shen, Chuan; Meng, Zhefeng; Zheng, Jianming; Jia, Yanhong; Chen, Shaolong; Zhang, Xiao; Zhu, Mengqi; Zheng, Jiangjiang; Song, Zhangzhang; et al. (Journal of hepatology, 2018)
[Display omitted] •Detectable HBV-RNA in serum of NUC successfully treated patients.•Serum HBV-RNA is indicative of the transcriptional activity of cccDNA.•Quasispecies of serum HBV-RNA and intrahepatic HBV-RNA are similar.•Levels of HBV-RNA correlate with histopathological scores. In diagnostics, serum hepatitis B virus (HBV)-RNA levels are valuable when the HBV-DNA load in circulation is effectively suppressed by nucleos(t)ide analogue (NUC) therapy. This study aimed to determine the intrahepatic viral replication activity reflected in serum HBV-RNA and whether HBV-RNA contributes to liver histological changes in patients treated with NUC. A cross-sectional set of serum and liver biopsy samples was obtained from patients treated with entecavir, who had undetectable levels of serum HBV-DNA. The correlations between serum HBV-RNA concentration and levels of peripheral and intrahepatic viral replicative forms, as well as histological scores, were analyzed. Quasispecies of serum HBV-RNA and intrahepatic viral replicative forms were examined by deep sequencing. HBV-RNA-positive hepatocytes were visualized by in situ hybridization. Serum HBV-RNA was detected in 35 of 47 patients (74.47%, 2.33–4.80log10copies/ml). These levels correlated not only with the intrahepatic HBV-RNA level and the ratio of intrahepatic HBV-RNA to covalently closed circular DNA (cccDNA), but also with the histological scores for grading and staging. Regarding quasispecies, serum HBV-RNA was dynamic and more genetically homogenous to simultaneously sampled intrahepatic HBV-RNA than to the cccDNA pool. In situ histology revealed that HBV-RNA–positive hepatocytes were clustered in foci, sporadically distributed across the lobules, and co-localized with hepatitis B surface antigen. Serum HBV-RNA levels reflect intrahepatic viral transcriptional activity and are associated with liver histopathology in patients receiving NUC therapy. Our study sheds light on the nature of HBV-RNA in the pathogenesis of chronic HBV infection and has implications for the management of chronic hepatitis B during NUC therapy. Serum HBV-RNA levels are indicative of the intrahepatic transcriptional activity of covalently closed circular DNA and are associated with liver histological changes in patients with chronic B hepatitis who are receiving nucleos(t)ide analogue therapy.